Augmented Reality, Embodied Cognition and Learning - Invitto, Sara; Spada, Italo; De Paolis, Lucio Tommaso (Augmented and Virtual Reality, 2015)
Augmented Reality allows a more detailed understanding of a learning object. Aim of this work was to analyse embodied cognition of the learning object, when it is presented in 2D or in 3D presentation in AR. Our sample was composed by University Students that differed with respect to the knowledge of plankton (naïve and competent condition). The subjects had to manipulate in AR some Application about plankton. After the AR manipulation, the subjects had to perform a recognition task during an EEG recording. We examined Event Related Potential P1, N2 and P3 components. Main result of the study was a significant change in amplitude in the parietal and central left lobe in all components in direction of greater amplitude in naïve condition. We interpret these results like a modulatory effect in the interaction with augmented reality application.